Disentangling Unusual Catalytic Properties and the Role of the [4Fe-4S] Cluster of Three Endonuclease III from the Extremophile D. radiodurans - Rollo, Filipe (2022)
Funding Information: This work was supported by FCT—Fundação para a Ciência e a Tecnologia, I.P., through MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020, UIDP/04612/2020) and LS4FUTURE Associated Laboratory (LA/P/0087/2020), research projects PTDC/QUI/BIQ/100007/2008, PTDC/BBB-BEP/0561/2014, PTDC/BIA-BFS/31026/2017, post doc fellowhip SFRH/BPD/97493/2013 (EM) and PhD fellowship SFRH/BD/132966/2017 (FR). Funding is also acknowledged for the TIMB3 project, European Union’s Horizon 2020 research and innovation program, under grant agreement No 810856. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.